PENGARUH STRUKTUR MODAL, LAMA USAHA DAN JUMLAH TENAGA KERJA TERHADAP LABA PADA HOME INDUSTRY TAS DI KABUPATEN GRESIK - Hidayatul Mahzunah (JURNAL MANAJERIAL, 2017)
This research aims to influence the capital structure, the old business, and labor to profits at home Gresik bag industry. The population in this study of 120 self-employed home industry bags in Gresik, using Stratifed Proportionate Random Sampling, then obtained 89 samples of self-employed home industry in Gresik type bag. Researchers also tested three independent variables, namely capital structure, long effort and the amount of labor that affect earnings. The purpose of this study the influence of the capital structure, the old business, and labor to profit by using multiple linear regression analysis. These results indicate variable capital structure does not affect the profit and old variable effort and affect the amount of labor.